Pengaruh Lingkungan Kerja Terhadap Kinerja Pegawai (Studi Kasus Kantor Dinas Cipta Karya, Tata Ruang dan Pertanahan Provinsi DKI Jakarta Tahun 2024) - Tria Izati; Endang Taufiqurahman (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Human resources are the most important element in an organization because they play a direct role in the sustainability and operational effectiveness, so organizations need to pay attention to the work environment as one of the factors that can affect employee performance. This study aims to analyze the condition of the work environment, measure the level of employee performance, and determine and empirically test the extent of the influence of the work environment on employee performance at the Office of Public Works, Spatial Planning, and Land Affairs of DKI Jakarta Province in 2024. Data collection was carried out using the entire population or saturated sample, namely 27 employees, with a descriptive quantitative approach through simple linear regression analysis. The analysis results show a t-value of 14.641 > t-table 2.060, so it can be concluded that the work environment variable (X) has a significant effect on the employee performance variable (Y). The coefficient of determination (R Square) value of 0.896 indicates that the work environment affects employee performance by 89.6%, while the remaining percentage is influenced by other variables outside this study.